Chemically Recyclable CO2‐Based Solid Polyesters with Facile Property Tunability. Issue 20 (19th October 2022) - Lou, Yongjia; Xu, Jialin; Xu, Luyan; Chen, Zhuo; Lin, Bo‐Lin
Abstract : Back Cover : In article 2200341, Bo‐Lin Lin and co‐workers discover a completely chemically recyclable polyester with high molecular weight, which originates from inexpensive CO2 and 1, 3‐butadiene. Furthermore, the material properties can be tailored via photo‐initiated post‐polymerization modification, which causes light blue fluorescence.